2020
DOI: 10.1037/pag0000441
|View full text |Cite
|
Sign up to set email alerts
|

Task characteristics influence facial emotion recognition age-effects: A meta-analytic review.

Abstract: Relative to their young counterparts, older adults are poorer at recognizing facial expressions. A 2008 meta-analysis of 17 facial emotion recognition data sets showed that these age-related difficulties are not uniform. Rather, they are greatest for the emotions of anger, fear, and sadness, comparative with happiness and surprise, with no age-effect found for disgust. Since then, there have been many methodological advances in assessing emotion recognition. The current comprehensive meta-analysis systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
69
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 153 publications
16
69
4
Order By: Relevance
“…They engaged a neural network that comprised bilateral insula, inferior frontal gyrus, and anterior cingulate, core nodes of the salience network (Menon, 2015; Menon et al, 2010), with cognitive empathy to negative emotions. This finding aligns with behavioral evidence that older compared to younger adults experience greater difficulty with processing negative emotions than with positive emotions (Hayes et al, 2020; Ruffman et al, 2008). Our findings also corroborate evidence of increased prefrontal cortex and insula activity for negative emotions in older adults, possibly reflecting more processing effort for and/or greater salient response when processing negative compared to positive stimuli with advanced age (Ebner et al, 2012; Ziaei et al, 2016a).…”
Section: Discussionsupporting
confidence: 88%
“…They engaged a neural network that comprised bilateral insula, inferior frontal gyrus, and anterior cingulate, core nodes of the salience network (Menon, 2015; Menon et al, 2010), with cognitive empathy to negative emotions. This finding aligns with behavioral evidence that older compared to younger adults experience greater difficulty with processing negative emotions than with positive emotions (Hayes et al, 2020; Ruffman et al, 2008). Our findings also corroborate evidence of increased prefrontal cortex and insula activity for negative emotions in older adults, possibly reflecting more processing effort for and/or greater salient response when processing negative compared to positive stimuli with advanced age (Ebner et al, 2012; Ziaei et al, 2016a).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the combination of genetics and neuroimaging in a study of the association between variants of genetic loci linked to SSD and SC in healthy individuals found that those with an increased risk score (taking into account the combined risk of such genetic loci) presented changes in the ACC when evaluating episodic memory and changes in the PCC when the ToM was evaluated (162). Some inconsistencies across studies were observed both in neuroimaging correlates and behavioral performance of SC in SSD and ASD, which can partly be the results of differences in task design: task characteristics have been shown to have an influence on outcomes and interpretation of social cognition performance assessment, and the choice of appropriate measures, balancing task sensitivity and ecological validity, represents an important factor that should be consistently taken account in the design of future studies (163). Moreover, it is possible that isolating SC in different components, such as emotion processing and ToM, might not be ideal, as in the realworld context of interpersonal relationships all these separate domains are likely to be involved in determining social behaviors (164).…”
Section: Discussionmentioning
confidence: 99%
“…Some inconsistencies across studies were observed both in neuroimaging correlates and behavioral performance of SC in SSD and ASD, which can partly be the results of differences in task design: task characteristics have been shown to have an influence on outcomes and interpretation of social cognition performance assessment, and the choice of appropriate measures, balancing task sensitivity and ecological validity, represents an important factor that should be consistently taken account in the design of future studies ( 163 ). Moreover, it is possible that isolating SC in different components, such as emotion processing and ToM, might not be ideal, as in the real-world context of interpersonal relationships all these separate domains are likely to be involved in determining social behaviors ( 164 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social cognitive impairment is now recognized to be a common and often debilitating feature of many clinical disorders, including many neurological, psychiatric, and developmental disorders 1 . There is also a large literature showing that social cognitive difficulties are evident in normal adult aging with moderate age effects identified in meta‐analytic reviews of this literature 3‐5 …”
Section: Introductionmentioning
confidence: 99%
“…1 There is also a large literature showing that social cognitive difficulties are evident in normal adult aging with moderate age effects identified in meta-analytic reviews of this literature. [3][4][5] Theory of mind (ToM), one of the core domains of social cognitive function, 1 refers to the ability to infer the mental state of another person and to appreciate that another person may hold a belief that differs from their own understanding of reality. 6 Older adults generally perform more poorly than younger adults on tests that index this construct, and these age-related differences persist even after controlling for broader age-related cognitive changes.…”
mentioning
confidence: 99%